2015
DOI: 10.5931/djim.v11i0.5516
|View full text |Cite
|
Sign up to set email alerts
|

Managing Print-Based Weeding Projects in Academic Libraries

Abstract: "Weeding" is the process of removing information resources from a collection. As a public relations quagmire, it is one of the most challenging tasks that an information manager may face. With the rise of election resources, printbased weeding projects are on the rise. It is integral that information managers have the necessary skills to carry out this endeavour. This paper examines the best practices for managing a print-based weeding project in an academic library, based on recent literature and the author's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Humanities faculty and researchers in the humanistic social science disciplines are the most outspoken groups when libraries decide to mass weed print collections. Many librarians mistakenly believe this is simply an emotional attachment that must be handled through better public relations or achieving faculty "buy-in" (Agee, 2017;Lynd, 2015;Metz & Gray, 2005;Young, 2009). While public relations are important for any library project, the presenters' research has shown that the concerns expressed by faculty during such projects are thoughtful and reasonable (McAllister & Scherlen, 2017).…”
Section: Research and Case Studymentioning
confidence: 99%
“…Humanities faculty and researchers in the humanistic social science disciplines are the most outspoken groups when libraries decide to mass weed print collections. Many librarians mistakenly believe this is simply an emotional attachment that must be handled through better public relations or achieving faculty "buy-in" (Agee, 2017;Lynd, 2015;Metz & Gray, 2005;Young, 2009). While public relations are important for any library project, the presenters' research has shown that the concerns expressed by faculty during such projects are thoughtful and reasonable (McAllister & Scherlen, 2017).…”
Section: Research and Case Studymentioning
confidence: 99%
“…Of interest, library literature shows that less-than-positive reactions by librarians to professors wanting input into deselection of their book resources is common. Hence, there are plenty of articles offering librarian-to-librarian inside advice on controlling patron reactions and maintaining resolve against naysayers to assure completion of the weeding project (Metz and Gray 2005;Intner 2006;McCormack 2008;Young 2009;Lynd 2015). And too many weeding-related publications, it was discovered, are unfortunately short on self-criticism and long on anecdotes, cheerleading, and misplaced confidence, avoiding the uncomfortable question of whether users might be appropriate participants in the deselection process (Handis 2007;Raphael 2013).…”
Section: Literature Reviewmentioning
confidence: 99%